Empowering minds: Harnessing the potential of cognitive field independence and dependence in STEM education - Rashidin Idris; Juppri Bacotang; Priyalatha Govindasamy; Suppiah Nachiappan (Human Resource Management Academic Research Society (HRMARS), 2023)
The purpose of this article is to discuss the importance of cognitive field independence and field dependency in STEM (Science, Technology, Engineering, and Mathematics) education. It discusses the critical topic of cognitive types and their impact on STEM learning and problemsolving. This study intends to illuminate how educators might harness these cognitive features to empower students in their STEM learning journeys by investigating the characteristics and benefits of field independence and reliance. The study focuses on the success of fieldindependent learners in analytical and abstract thinking, as opposed to field-dependent learners' ability for holistic and context-based comprehension. It also looks into methodologies and pedagogical approaches for accommodating diverse cognitive styles in order to create inclusive and engaging learning environments. Recognizing and cultivating the qualities of field independence and dependency can help educators unlock students' full potential and foster a diverse range of problem-solving skills in the STEM industry. Finally, this paper emphasizes the necessity of recognizing cognitive variety and harnessing it as a significant tool for increasing creativity and achievement in STEM education.